1984
DOI: 10.1017/s0022029900023396
|View full text |Cite
|
Sign up to set email alerts
|

A microassay for the syneresis of cheese curd

Abstract: SummaryA micro scale syneresis assay, using the natural optical density of the whey released as a trace, is reported. This assay is suitable for use with raw, reconstituted skim-milk (RSM) or artificial milk. Using RSM the reproducibility and accuracy of the method compared favourably with larger scale laboratory assays. When the method was used to investigate the syneresis properties of artificial micelle milk (AMM), the rate and extent of syneresis and response to a major variable such as pH were very simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 4 publications
5
15
0
Order By: Relevance
“…I and II). A negative effect of ren.pH on drainage has been already reported [20,22,23,25,31,40]. However these authors did not observe the late positive effect we describe, as they studied whey drainage for shorter draining times, up to 150 min only.…”
Section: The Renph Effectsupporting
confidence: 40%
“…I and II). A negative effect of ren.pH on drainage has been already reported [20,22,23,25,31,40]. However these authors did not observe the late positive effect we describe, as they studied whey drainage for shorter draining times, up to 150 min only.…”
Section: The Renph Effectsupporting
confidence: 40%
“…It has been reported that the firmness at cutting has no significant influence on syneresis rate (Hansen et al, 2010;Pearse, Mackinlay, Hall, & Linklater, 1984;Storry & Ford, 1982), and Johnson et al (2001) showed there was a slightly increase of cheese yield when the coagulum was cut at higher firmness.…”
Section: Initial Firmness Of Cheese Curdmentioning
confidence: 99%
“…Rennet treatment (1 fi\ undiluted rennet ml" 1 AMM) and syneresis measurements were performed on 4 ml portions of AMM using the microscale optical density dilution assay described by Pearse et al (1984). Syneresis of each milk was measured twice in separate syneresis runs on the same day.…”
Section: Syneresis Determinationmentioning
confidence: 99%